Finite Element Analysis of a Wheel Assembly for a Pipeline Corrosion Inspection Robot - Mohd Amir Shazwan, Hashim; Shawkat Ali, Allybocus; Lim, Khai Hen; Muhammad Izzat Nor, Ma'arof; Intan Syaqirah, Mohd Zulkifli; Girma, Tadesse Chala (INTI International University, 2023)
A pipeline network is critical in allowing for transportation of matter for various applications. One of the major issues of concern for this area is with respect to corrosion and/erosion of the pipelines. A pipeline corrosion inspection robot is commonly used for reconnaissance purposes. The aim of this study was to determine the stress distribution and the safety factor at the back wheel assembly of the pipeline corrosion inspection robot during operation. The assessment was made with respect to operation within the pipeline and under the pressure of flowing fluid. The back wheel assembly was designed via Computer-Aided Design (CAD) and the Finite Element Analysis (FEA) was conducted via ANSYS Software. The result showed that recorded equivalent stress, total deformation and safety factor of the back wheel assembly are 192.35Ma, 0.06534mm, and 1.43 respectively. Thus, this result clearly indicated that the back wheel assembly is indeed capable in performing operations within the pipeline without experiencing unwanted damage. In short, the design of the back wheel assembly of the pipeline corrosion inspection robot is optimized. For future studies, assessments on the back wheel assembly under various loading conditions could be performed.